Studi Eksperimental Lekatan antara Beton dan Tulangan pada Beton Mutu Tinggi - Nuroji, Nuroji (MEDIA KOMUNIKASI TEKNIK SIPIL, 2004)
In recent years, concrete with compressive strength in excess of 50 MPa has been utilized in building construction. However, many empirical equations used to predict properties of concrete or design structure members are based on test using concrete with compressive strength less than 41 MPa. Applicability of this design equation for high strength concrete structures may lead to conservative or even unsafe design. One such example is the provision for calculating development length of reinforcing bars which is developed based on bond capacity of steel bars embedded in concrete.The research study was motivated by the lack of test data on bond performance of reinforcing bars embedded in high strength concrete especially those related to high-strength fly-ash concrete. More than 35 specimens with various concrete compressive strength fcÂ¢ and bar diameter (deformed and smooth bar) were tested. The result of this experimental shows that bond equation from ACI is too conservative for high strength concrete structures. Kata kunci: Lekatan beban dan tulangan, beton mutu tinggiPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2739 [How to cite: Nuroji, 2004, Studi Eksperimental Lekatan antara Beton dan Tulangan pada Beton Mutu Tinggi, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 27-37]